Pengembangan Bahan Ajar Tema Kerukunan dalam Bermasyarakat Berbasis Al-Qur'an Kelas 5 MI Munir Ismail Gondanglegi Malang - Azizi, Alfan Nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The existence of teaching materials that equipped with religious reinforcement such as the verses of Al-Qur'an, is an important thing for Madrasah Ibtidaiyah as an Islamic educational institution. In addition, there are some problems that threaten the existence of Bhineka Tunggal Ika, it shows that the value of harmony of Indonesian society goes down. The development of teaching materials on the theme of Harmony in Community Based on Al-Qur'an is one of the efforts to solve the problems. This research was conducted with quantitative approach with Research and Development type. It aims to produce a product in the form of teaching materials on the theme of Harmony in Community. In its implementation, this research refers to the development model that is developed by Sugiyono, and data collecting technique is a questionnaire on two validators and experiments. The result of this research is the creation of a teaching materials product feasible and effective. This is evidenced by (1) assessment of material feasibility test on material expert validator, obtained by percentage of 78.3% with good qualification, (2) assessment of feasibility test at design expert, obtained by percentage of 84,4% in good qualification, and (3) ) while the effectiveness of the development of teaching materials, based on the results of field trials showed that the difference in the average gain of the experimental group is 10.3 and the average gain of the control group is 5.89, then the result is analyzed by F-test for determining the homogeneity, and the homogeneity of both groups is obtained. Furthermore, T-test is done to determine the significance of difference of average gain of both groups. The result of T-test can be concluded that the teaching materials on the theme of Harmony in Community Based on Al-Qur'an is declared effective, so it can improve the student learning outcomes.